Bifunctional Pt/Hβ catalyzed alkylation and hydrodeoxygenation of phenol and cyclohexanol in one-pot to synthesize high-density fuels. (15th February 2023) - Shen, Zhensheng; Zhang, Gewei; Shi, Chengxiang; Qu, Juncong; Pan, Lun; Huang, Zhenfeng; Zhang, Xiangwen; Zou, Ji-Jun
Highlights: One-pot preparation of polycycloalkane high-density fuels. Acidity and mesoporous structure can accelerate alkylation rate. The yield of bicyclic and tricyclic rings in the final product can reach 83.42%. The catalysts can couple other acid- and metal-catalyzed reactions. Abstract: Synthesis of fuels from lignin bio-oil feedstock significantly alleviates energy crises and environmental pollution. Phenol is the simplest model compound for lignin bio-oil feedstocks, and the synthesis of fuel precursors from phenol through alkylation has received increasing attention. Here we report a one-pot strategy for preparing polycyclic alkane high-density fuels from phenol and cyclohexanol over bifunctional Pt/Hβ catalyst by combining alkylation with following hydrodeoxygenation (HDO). The activity of different zeolites for catalyzing the alkylation of phenol and cyclohexanol was explored. It was found that the larger pore size of alkali treated Hβ would not limit the production of polycyclic compounds, and good acid content in a particular mesoporous specific surface area can speed up the reaction rate. The one-pot reaction conditions were then optimized. When the alkali treatment concentration is 0.2 mol/L, the metal loading is 0.2 wt%, and the molar ratio of phenol and cyclohexanol is 1:1, the highest conversion of phenol can reach more than 83 %. The selectivity of alkylphenol can reach more than 97 %, and the yield of bicyclic and tricyclic rings in the final product after HDO can reach 83.42 %. The bifunctional catalyst can also realize the coupling of other acid-catalyzed carbon growth reactions and metal-catalyzed HDO reactions, which allows the direct synthesis of fuel from lignin oil or other biomass compounds.